2007
DOI: 10.1124/dmd.107.017954
|View full text |Cite
|
Sign up to set email alerts
|

Aryl-Propionamide-Derived Selective Androgen Receptor Modulators: Liquid Chromatography-Tandem Mass Spectrometry Characterization of the in Vitro Synthesized Metabolites for Doping Control Purposes

Abstract: ABSTRACT:Selective androgen receptor modulators (SARM) are a prominent group of compounds for being misused in sports owing to their advantageous anabolic properties and reduced side effects. To target the preventive doping control analysis in relevant compounds, the challenge is to predict the metabolic fate of a new compound. For aryl-propionamide-derived SARM, an in vitro assay employing microsomal and S9 human liver enzymes was developed to simulate phase-I and phase-II metabolic reactions. In vitro metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 28 publications
6
85
0
Order By: Relevance
“…Blood samples were collected at time 0 (immediately prior to SARM administration) and at 5, 10, 15, 30, and 45 min, and 1, 1.5, 2, 2.5, 3,4,5,6,8,12,18,24,48,72 and 96 h post SARMs administration. Prior to drawing each sample of blood for analysis, 10 mL of blood was aspirated and discarded from the catheter and T-Port extension set Figure 1.…”
Section: Administration and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were collected at time 0 (immediately prior to SARM administration) and at 5, 10, 15, 30, and 45 min, and 1, 1.5, 2, 2.5, 3,4,5,6,8,12,18,24,48,72 and 96 h post SARMs administration. Prior to drawing each sample of blood for analysis, 10 mL of blood was aspirated and discarded from the catheter and T-Port extension set Figure 1.…”
Section: Administration and Sample Collectionmentioning
confidence: 99%
“…[7] Furthermore, the identification of metabolites also corroborates that a substance has passed through a metabolic system and that an adverse finding is not caused by contamination of the sample. The metabolism of different SARMs of the arylpropionamide class has been studied in vitro in a variety of systems such as human liver microsomes, [8] equine liver microsomes, [9] bovine liver microsomes [10] and fungal incubates, [11] as well as in vivo in both human [12,13] and equine [14] urine. The three aforementioned in vivo studies showed that the SARMs were metabolized rapidly and extensively.…”
mentioning
confidence: 99%
“…A two-step approach whereby the first step (Phase I) used a mixture of human liver microsomal and S9 fractions in a phosphate buffer with NADPH, and for the second step (Phase II) either UD-PGA or PAPS were added for glucuronidation or sulfation, respectively. In this example, the application was for the bioactivation and biodegradation of selective AR modulators (Kuuranne et al, 2008 The method of S9 incubation S9 may be co-incubated with the cells and chemical (Li et al, 2011) or a chemical may be needs to be considered pre-incubated with S9 and then the extract applied to the assay (Taxvig et al, 2011). In general, co-incubation is a time-saving approach but may lead to cytotoxicity in the assay system.…”
Section: State Of the Science On Novel In Vitro And In Vivo Screeningmentioning
confidence: 99%
“…For example, Kuuranne et al (2008) successfully used human S9 liver mixes on selective androgen receptor modulators (SARMs) to predict the in vivo marker metabolites. Similarly, bovine S9 mixes have been used with SARMs and showed that the metabolites formed also were found in vivo (De Rijke et al, in press).…”
Section: The Choice Of Species Providing S9mentioning
confidence: 99%
“…Poor pharmacokinetics is one of the reasons for the withdrawal of drug candidates from clinical trials (Kuuranne et al 2008). Thereby, the objective of this study was to develop a step-down passive avoidance test to investigate whether DMNG-3 could modulate impairment of learning and memory induced by scopolamine.…”
Section: Introductionmentioning
confidence: 99%